LEGAL AND REGULATORY APPROACHES IN ṢUKŪK ISSUANCE: A COMPARATIVE ANALYSIS (UUM Journal of Legal Studies, 2022)
The Ṣukūk structure seems to be closer to bonds structure. Many jurisdictions have applied bonds rules on Ṣukūk to permit its issuance without a specific and adequate legal framework. Proper Ṣukūk legal and regulatory frameworks are quite needed to distinguish Ṣukūk from bonds. The purpose of this article is to compare the legal and regulatory frameworks of Ṣukūk issuance in different countries and to examine the core provisions that allow the direct issuance of Ṣukūk. This article is based on a comparative method which analyses the main legal and regulatory approaches that underpinned the issuance of Ṣukūk in some countries. The required data is gathered from the relevant laws and regulations of countries like Indonesia, Malaysia and U.K, law books, and articles. The findings of this article reveal that Ṣukūk has been regulated under two approaches, namely by enacting a separate law or amending the existing legislations. This study has also highlighted the models to follow in the event there was a need to regulate Ṣukūk at the same level as conventional bonds, so as to allow for Ṣukūk issuance. It provides a wide range of the best lessons of some jurisdictions that have implemented the regulatory framework of Ṣukūk in order to strengthen the local rules for Ṣukūk market position.